Analysis Of Information Retrieval System In The Repository Of The State Islamic University (UIN) Raden Intan Lampung - Yunita, Irva; Nawafella A.P, Reza (KnE Social Sciences, 2024)
This research discusses the information retrieval system through the UIN Raden Intan Lampung Repository.This research uses a qualitative research design with data collection using literature study, documentation and observation. The information retrieval system in the UIN Raden Intan Lampung repository can be done through searching and browsing. Searching the repository can be done with simple search and advanced search. In simple search, users can search by entering keywords, title, author and subject. Searching via searching can also use Boolean operators, namely AND, OR, and NOT. Browsing at the UIN Raden Intan Lampung Repository can be done by year, subject, division and author. Furthermore, searching for documents via browsing by author's name is also not optimal, this is due to differences in author name metadata input to different repositories, namely there are names that are reversed. and not reversed, so this also requires user accuracy in searching documents Keywords: Information retrieval, Repository, Retrieval system